Determination Of Marketing Strategy For Distance Learning In The Island : Determination Of Marketing Strategy For Distance Learning In The Island - Anfas Anfas; Mohbir Umasugi; Lisda Ariani Simabur (Institute of Computer Science (IOCS), 2020)
This research aims to learn effective promotion strategies in attracting people on the island to learn through distance learning at UT. This research was conducted using a quantitative approach. Research data obtained from secondary data that has been available on the UT SIPELAPOR application. Based on the results of the study, it showed that the majority of students first got information about UT, namely 1,399 students (48.76%) through friends, 575 students (20.04%) through families, and 388 students (13, 52%) through the Site UT Web. From this data, it can be concluded that: (1) Word of mouth promotion strategies (WOM) are very appropriate in promoting distance learning on islands. (2) Word of mouth (WOM) can be done in two ways, first, the hearing is done by visiting directly to market segments. The second is to utilize online social media (e-WOM). This study has implications aimed at UT management in improving promotional communication through WOM. So that the target of increasing the number of students is realized. This study shows how to determine the strategy of promoting education through WOM in accordance with the characteristics and geographical conditions of UPBJJ in the archipelago in an effort to increase the number of students.